PROMIS PF CAT Provides Consistent Outcomes Assessment with Excellent Precision and Efficiency - Rizzo, Toni (MD Conference Express, 2014)
There is a tangible need for improved tools to measure patient outcomes after treatment of foot and ankle disorders. One of those is the Patient-Reported Outcomes Measurement Information (PROMIS) physical function computerized adaptive testing (PF CAT), which has been validated for orthopaedic patients, as well as for lower extremity patients. This article discusses a study comparing the psychometric properties and efficiency of the PF CAT with the Foot Function Index and Foot and Ankle Ability Measure.